"Struck down by cancer with no old life to fall back on" a clinical study of illness experiences among Norwegian adolescent and young adult cancer survivors investigating the ethical implications of their illness narratives. Issue 4 (9th December 2022) - Hjulstad, Kristine; Bondevik, Hilde; Hem, Marit Helene; Nortvedt, Per
Abstract: Background: Cancer is a leading cause of death among people 15–24 years of age. Increasing numbers of cancer patients survive. Extensive cancer therapy may cause wide‐ranging somatic and psychosocial challenges in the lives of the survivors. Research indicates adolescent and young adult cancer (AYA) survivors need to be seen as a distinctive group of survivors having unique health care needs. The existing literature suggests the need for specific follow‐up care programs addressing the challenges of AYAs and providing them access to specialized after care, as well as a need to explore AYA cancer survivors' own illness experiences. Aims: Through the theoretical lens of narrative medicine and care ethics, our purpose was to investigate the particular challenges encountered by the AYA cancer survivors, and how they view themselves in light of their illness experiences. We ask how AYA cancer survivors are met and understood by their medical professionals? Methods: This study applied a qualitative method using a narrative research design by collecting self‐stories of illness in order to conceptualize human experiences of illness among AYA cancer survivors. Eight in‐depth interviews were conducted using a narrative analysis according to the narrative plots of restitution, chaos and quest, as suggested by Arthur Frank. Results: Hopelessness and a struggle to take part in the activities of daily life as survivors of cancer were revealed. Too ill to fully take part in the society, the AYA cancer survivors strive to be understood for what they are, namely young survivors. Conclusion: The survivors'stories reveal a moral imperative that needs to be honored by medical professionals in order to improve cancer care. Cancer survivorship may be a lifelong process necessitating long‐term follow‐up care. With the lack of specific care programs for AYA cancer survivors, follow‐up care is provided by general practitioners or other medical professionals, who often lack expertise in the unique challenges faced by AYA survivors. Because they feel their needs are unmet and their stories not understood, the AYA survivors might experience a sense of abandonment. By adopting a care ethics and narrative medicine approach we provide medical professionals a theoretical framework to better understand and care for AYA cancer survivors. Clinical trial number is 2012/1141.